Effects of Aging and Adult-Onset Hearing Loss on Cortical Auditory Regions - Cardin, Velia (Frontiers in Neuroscience, 2016)
Hearing loss is a common feature in human ageing. It has been argued that dysfunctions in central processing are important contributing factors to hearing loss during older age. Ageing also has well documented consequences for neural structure and function, but it is not clear how these effects interact with those that arise as a consequence of hearing loss. This paper reviews the effects of ageing and adult-onset hearing loss in the structure and function of cortical auditory regions. The evidence reviewed suggests that ageing and hearing loss result in atrophy of cortical auditory regions and stronger engagement of networks involved in the detection of salient events, adaptive control and re-allocation of attention. These cortical mechanisms are engaged during listening in effortful conditions in normal hearing individuals. Therefore, as a consequence of ageing and hearing loss, all listening becomes effortful and cognitive load is constantly high, reducing the amount of available cognitive resources. This constant effortful listening and reduced cognitive spare capacity could be what accelerates cognitive decline in older adults with hearing loss.